Pelaksanaan Peraturan Daerah Terkait Pengelolaan Sampah Rumah Tangga di Kota Kupang - Liky Ledoh (Jurnal Inovasi Kebijakan, 2021)
The increase in the amount of waste has resulted in problems with waste services as regulated in the Kupang City Regional Regulation (Perda) number 13 of 2000, number 3 of 2011 and number 4 in 2011. However, the results of the Adipura Assessment in 2019 placed Kupang City in 5th place with the title of the Dirtiest City in Indonesia. This study aims to present the implementation of Regional Regulation number 13 of 2000, number 3 of 2011 and number 4 of 2011 in Kupang City. The research method uses quantitative and qualitative descriptive analysis, by describing general information from the findings based on primary and secondary data. The results of the study show that the implementation of regional regulations related to waste has not been maximized due to the unavailability of Regional Policies and Strategies, as well as the Master Plan for Waste Management as a reference for handling and reducing waste in Kupang City. Implementation of Regional Regulation number 3 of 2011 and Regional Regulation number 4 of 2011 is also not maximized and overlaps because it has not been supported by derivative rules. The need for changes to Regional Regulation number 13 of 2000 related to the unit of levy value because it is not in accordance with current conditions.